Experimental investigation of seismic behavior of ultra-high performance steel fiber reinforced concrete columns. (1st December 2017) - Xu, Shenchun; Wu, Chengqing; Liu, Zhongxian; Han, Kunpeng; Su, Yu; Zhao, Jian; Li, Jianchun
Highlights: Cyclic loading test on 14 UHPSFRC columns were conducted. Failure characteristic and mechanical behavior of 14 UHPSFRC columns were analysed. The parametric study on the seismic behavior of UHPSFRC columns was conducted. Abstract: This paper presents an experimental study on seismic behavior of ultra-high performance steel fiber reinforced concrete (UHPSFRC) columns. Based on a series of cyclic loading tests on 14 UHPSFRC specimens subjected to combined static axial loading and cyclic lateral loading, the investigation and analysis have been carried out on crack status, failure modes, hysteretic loops, skeleton curves, strength and stiffness degradation, energy dissipation capacity and ductility of UHPSFRC columns. The influence of stirrup spacing, type of stirrup, axial compression ratio and shear span ratio on the seismic performance of UHPSFRC columns was also investigated in details. The experiment results show that three typical failure modes are observed, i.e., flexural, flexural-shear and shear failure mode. The existence of steel fiber could prevent the cracked concrete from spalling efficiently and delay the bulking of longitudinal reinforcement further. It noteworthy that the limit plastic drift ratio of all columns changes from 0.036 to 0.061, indicating that the UHPSFRC columns represent a good ductility which is obviously different from the conventional high strength concrete columns that exhibit much more brittleness with the increase of strength.